Interlaced rosette-like MoS2/Ni3S2/NiFe-LDH grown on nickel foam: A bifunctional electrocatalyst for hydrogen production by urea-assisted electrolysis. (1st January 2020) - He, Maoxiao; Hu, Shengnan; Feng, Chuanqi; Wu, Huimin; Liu, Huakun; Mei, He
Abstract: In targeting the most important energy and environmental issues in current society, the development of low-cost, bifunctional electrocatalysts for urea-assisted electrocatalytic hydrogen (H2 ) production is an urgent and challenging task. In this work, interlaced rosette-like MoS2 /Ni3 S2 /NiFe-layered double hydroxide/nickel foam (LDH/NF) is successfully synthesized by a two-step hydrothermal reaction. Due to its unique interlaced heterostructure, MoS2 /Ni3 S2 /NiFe-LDH/NF exhibits excellent bifunctional catalytic activity towards the urea oxidation reaction (UOR) and the hydrogen evolution reaction (HER) in 1.0 M KOH with 0.5 M urea. In a concurrent two-electrode electrolyser (MoS2 /Ni3 S2 /NiFe-LDH/NF(+, -)), only voltage of 1.343 V is required to reach 50 mA cm −2, which is 216 mV lower than for pure water splitting. Furthermore, after 16 h of urea electrolysis in 1.0 M KOH with 0.5 M urea, the current density remains at 98% of the original value. Thus, the catalyst is not only favorable for H2 production, but also has great significance for the problem of urea-rich wastewater treatment. Highlights: MoS2 /Ni3 S2 /NiFe-LDH/NF was synthesized for efficient hydrogen production. MoS2 /Ni3 S2 /NiFe-LDH/NF exhibited excellent catalytic activity towards both HER and UOR. The efficiency of hydrogen production by urea-assisted electrolysis is higher than pure water splitting.